King or royal family? Testing for species boundaries in the King Cobra, Ophiophagus hanah (Cantor, 1836), using morphology and multilocus DNA analyses - P. Gowri, Shankar; Priyanka, Swamy; Rhiannon C., Williams; S.R., Ganesh; Matt, Moss; Jacob, Hoglund; Indraneil, Das; Gunanidhi, Sahoo; S.P., Vijayakumar; Kartik, Shanker; Wolfgang, Wüster; Sushil K., Dutta (Elsivier, 2021)
In widespread species, the diverse ecological conditions in which the populations occur, and the presence of many potential geographical barriers through their range are expected to have created ample opportunities for the evolution of distinct, often cryptic lineages. In this work, we tested for species boundaries in one such widespread species, the king cobra, Ophiophagus hannah (Cantor, 1836), a largely tropical elapid snake distributed across the Oriental realm. Based on extensive geographical sampling across most of the range of the species, we initially tested for candidate species (CS) using Maximum-Likelihood analysis of mitochondrial genes. We then tested the resulting CS using both morphological data and sequences of three single-copy nuclear genes. We used snapclust to determine the optimal number of clusters in the nuclear dataset, and Bayesian Phylogenetics and Phylogeography (BPP) to test for likely species status. We used non-metric multidimensional scaling (nMDS) analysis for discerning morphological separation. We recovered four independently evolving, geographically separated lineages that we consider Confirmed Candidate Species: (1) Western Ghats lineage; (2) Indo-Chinese lineage (3) Indo-Malayan lineage; (4) Luzon Island lineage, in the Philippine Archipelago. We discuss patterns of lineage divergence, particularly in the context of low morphological divergence, and the conservation implications of recognizing several endemic king cobra lineages.